Violência contra crianças e adolescentes do sexo feminino narradas pela mídia impressa paraense - COSTA, Raine Marques da (2019)
INTRODUCTION: Violence is a phenomenon that reaches all humankind and it is present in every society throughout history being known as a complex occurrence and caused by many factors and it needs to be understood amid the historical and cultural context in which it happens. Women, elders, children and adolescents are considered the most vulnerable to violence groups. Media has recently shown a scaring advance of violence in society but, at the same time, it is growing the comprehension that violent attitudes can not be naturalized but seen as human rights violations. AIM: To analyze violence against female children and adolescents narrated by print media from the State of Para. METHODOLOGY: Descriptive study in a quantitative approach that has examined 730 copies of O Liberal newspaper from which were extracted 334 violence against women notes that occurred from 2016 to 2017, 99 from those were about violence against female children and adolescent from the State of Para. Data was collected from newspaper notes and then organized in a system with the support of Microsoft Office Excel 2010 program. The data obtained were presented in the form of maps, graphs and tables. The analysis of the data was carried out in the light of the publications that version about the subject studied. FINDINGS: Findings have shown violence victims and authors profiles, most prevalent types of violence and nursing care on violence against female children and adolescents. Study has exposed that most violence cases notified by print media have victimized children between the age of 1 to 12 years old (61,86%); adolescents from 12 to 18 years old accounted for 38,14% from the cases. Most prevalent age group has been from 10 to 12 years old. Sexual violence has been most usual violence accounting for 59,60% cases; children and adolescents’ residences have been the most usual place of occurrence (70,52%); rape the most used mean (61,26%); genitals the most body part affected (55,93%); and most cases have had victims’ known people as authors (47,40%). All days of the week have basically proportional cases rate with a slight increase thought the week and decrease in weekend. Violence authors have been mostly men (43,85%) with ages between 19 and 26 years old (27,96%) and married (53,85%). There has been no a predominant occupation among offenders. CONCLUSION: It is essential the role of print media in publishing important subjects for society, contributing to academic research and helping the development of strategic actions to restrain violence against children and adolescents giving them the right of a healthy growing.